Dynamics of Pulse Scenario in Bundelkhand Region of Uttar Pradesh: A Temporal Analysis - Sah, Uma; Dixit, G. P.; Kumar, Hemant; Ojha, Jitendra; Katiyar, Mohit; Singh, Vikrant; Dubey, S. K.; Singh, N. P. (Indian Journal of Extension Education, 2021)
The paper examines the temporal changes in the area, production and productivity of major pulse crops in Bundelkhand region of UP during last two decades (2000-2020). Published data on area, production and productivity was utilized for the purpose. Study period was divided into period-I (2000-10) and period II (2010-20) and overall period III (2000-2020). Consistent decline in overall pulse area (-0.64%) and production (-0.36%) was observed, however, the overall pulse productivity registered marginal upward trend (0.06%) during the analysis period (2000-20). Chickpea (-5.03% and -0.64 %) and lentil (-0.51% and -4.37%) crops registered highest decline in overall area and production respectively. Urdbean registered highest decline (-6.52%) in productivity during the said period. In contrast, mungbean crop followed by urdbean recorded highest growth in area (3.48%, 3.02%), and production (3.61%, 2.71%), while field pea registered highest growth in productivity (1.96%). Instability of pulse production over the study period was high (30.31%), however the instability in pulse area was low (11.7%). Analysis of inter district variation in pulse performance reflected decline in area and production of pulses in all districts except in Lalitpur. Inter district variations helped in identifying the potential districts in the Bundelkhand region of UP state.
Keywords: Pulses; Bundelkhand region; Temporal analysis; Instability analysis